High-energy impact and vapor recondensation history of the angrite parent body revealed by nickel isotopes - Ke Zhu; Akira Yamaguchi; Paolo A. Sossi; Audrey Bouvier; Lu Chen; Peng Ni (Proceedings of the National Academy of Sciences, 2025)
The angrite parent body (APB) is the most volatile-depleted among known differentiated bodies in the Solar System, yet the mechanisms responsible remain poorly constrained. Here, we present high-precision nickel (Ni) isotope data from a suite of angrite samples to reconstruct the APB’s volatile depletion history. Plutonic angrites contain unusually high proportions of metallic iron and exhibit chondritic δ 60/58 Ni values (0.202 ± 0.028‰; per mille mass-dependent 60 Ni/ 58 Ni deviation relative to National Institute of Standards and Technology (NIST) Standard Reference Material (SRM) 986). These observations are consistent with a homogeneous Ni isotope composition of the APB after core formation and the subsequent incorporation of endogenous core material in plutonic angrites. In contrast, a dunite and megacrystic olivines from volcanic angrites, derived from the mantle, display suprachondritic δ 60/58 Ni values (0.4 to 0.7‰). We argue that these values are consistent with Ni loss via evaporation during a high-energy impact that follows an initial stage of volatile loss from a magma ocean generated by 26 Al heating. Thermodynamic modeling confirms Ni to be more volatile than Mn, Fe, Si, and Mg during evaporation from silicate liquids, in agreement with the observed relative magnitude of isotopic fractionation. Volcanic angrite matrices show variable and often subchondritic δ 60/58 Ni values (down to −0.5‰), reflecting mixing with isotopically heavy megacrystic olivines and recondensation of light Ni vapor onto the crust. These findings imply that volatile elements are stratified (core–mantle–crust) in the APB and provide direct isotopic evidence for impact-driven vapor loss and recondensation on a differentiated planetary body.